Rivalry, reason, and revolution - James, Leonard Frank (New York, Pergamon, 1973)
One in a five volume series on the history of Western civilization, this volume traces the history of Europe and the United States from the twelfth to the eighteenth century.
Keywords: Europe -- History -- 1492-1648.; Europe -- History -- 1648-1789.; United States -- History -- Colonial period, ca. 1600-1775.; Europe -- History; United States -- History -- Colonial period, ca. 1600-1775.